Aberrant Peripheral Immune Function in a Good Syndrome Patient - Xian Chen; Jie-xin Zhang; Wen-wen Shang; Wei-ping Xie; Shu-xian Jin; Fang Wang (Journal of Immunology Research)
Good’s syndrome (GS) is often accompanied by recurrent respiratory infections and chronic diarrhea. The main purpose was to evaluate the peripheral immune status of a GS patient after thymoma resection. Twenty healthy volunteers were recruited as healthy controls (HCs). Flow cytometry was applied to determine the proportions of circuiting CD4+ T cells, CD8+ T cells, γδT cells, and regulatory T (Treg) cells in our GS patient. We also examined the proliferation capability of ex vivo CD4+ T cells and detected the levels of cytokines interferon- (IFN-) γ and interleukin-17A secreted by ex vivo immune cells from this GS patient. Compared with healthy control subjects, this GS patient had fewer B cells, an inverted ratio of CD4+/CD8+ cells, and more Treg cells in his peripheral blood. Additionally, the patient’s Vδ2 T cell levels were significantly decreased despite having a normal percentage of γδT cells. Ex vivo peripheral CD4+ T cells from the patient showed insufficient proliferation and division potential as well as excessive expression of PD-1. Moreover, IFN-γ was predominantly derived from CD8+ T cells in this GS patient, rather than from CD4+ T cells and γδT cells. This GS patient had impaired T and B cell immunological alternations and cytokine disruptions after thymectomy. Detailed research should focus on therapies that can adjust the immune status in such patients for a better outcome.